Lupus nephritis. Remissions and relapses. Long-term follow up of 84 patients - Gerardo Oscar Mogni; Marina Flavia Caputo; Yanina Bottinelli (Revista de Nefrología, Diálisis y Trasplante, 2014)
Introduction: Nephritis is the most common of all serious manifestations of SLE. The proliferative forms require immunosuppressive treatment, but responses are not consistent and exacerbations are frequent during or after the treatment has been completed. Methods: We retrospectively analyzed the evolution of a cohort of 84 patients with proliferative lupus nephritis with immunosuppressive treatment, in a long-term (up to 203 months) follow up. Were taken as basal: sex, age, latency between onset and diagnosis of SLE nephritis, serum complement, plasmatic creatinine and proteinuria. We evaluated: initial response to therapy, occurrence of relapse or recurrence and score at the end of the observation period. Results: Remission of initial nephritis was seen in 73% of the cases, although at the end of monitoring only 54% of patients were in remission. 45 patients had one episode of nephritis, 32 patients had two, and 7 patients had three. Most of the remissions took place during the maintenance period. Complete remission had better evolution than partial remission. High serum creatinine levels and proteinuria at baseline were indicators of bad prognosis. Oral Azathioprine was more effective than quarterly IV Cylophosphamide as maintenance therapy, despite of a high incidence of relapses. Mycophenolate was not more effective than Cyclophosphamide/azathioprine for the treatment of relapses or recurrences. Conclusions: Our results are similar to the literature. Extended follow up enables the evaluation of the long term result of the initial symptoms, any possible future outbreaks, the effectiveness of the treatment and its evolution after its interruption.